Toxicological analysis of acute pesticides poisoning among Moroccan population - Birich Bouchra (EDP Sciences, 2021)
The aim of this study is to evaluate the importance of toxicological analysis in acute intoxications by pesticides through the experience of the laboratory of the Poison Control and Pharmacovigilance Center of Morocco (CAPM). This is a retrospective study from January 2014 to September 2020, concerning suspected pesticides poisoning cases. The cholinesterase activity was measured in whole blood and the chromatographic analyzes (GC-MS and LC-MS-MS) were conducted in blood, urine and gastric lavage fluid. In this study, 398 tests were involved. The median age of the patients was 14 with an interquartile range of [4-26 years]. The sex ratio (F / M) was 1.5. The requests were from the region of Rabat-Salé-Kénitra in 82.8% of cases (north-western Morocco). The cholinesterase activity measurement was performed for 295 patients with low values in 3.7% of cases. The toxicological screening by GC-MS and LC-MS-MS detected the pesticide responsible of poisoning in 62 cases as insecticides in 38% of cases, redenticides (33% of cases) and herbicides (5% of cases). Toxicological analysis plays an essential role in the diagnosis and the management of acute pesticides poisoning. Interpretation of results is carried over by analyst with close cooperation with clinical toxicologist.